2008
DOI: 10.1016/j.atherosclerosis.2007.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II AT1 receptor blockade normalizes CD11b+ monocyte production in bone marrow of hypercholesterolemic monkeys

Abstract: The enhanced production of monocytes expressing pro-inflammatory markers such as the integrin CD11b in patients with hypercholesterolemia may promote vascular inflammation and exacerbate atherogenesis. The objective of the present study was to determine whether hypercholesterolemia stimulates the production of CD11b + monocytes in bone marrow, and whether the renin-angiotensin system participates in this process and thus provides a target for therapeutic intervention. The dietary induction of hypercholesterole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…11 However, the relative contribution of the BM renin-angiotensin system to hypercholesterolemia-associated monocytosis has not been fully investigated. 12 In the present study, we focused on the action of the AT 1 receptor expressed in BM cells and studied whether (1) Ang II affects the differentiation/proliferation from BM stem cells into monocyte-lineage cells, and (2) hypercholesterolemiaassociated monocytosis contributes to the development of AT 1 -mediated atherosclerosis. Our results demonstrated for the first time that (1) Ang II promotes M-CSF-induced differentiation from hematopoietic stem cells (HSCs; c-Kit ϩ Sca-1 ϩ Lin Ϫ ) into monocyte-lineage cells through upregulation of the M-CSF receptor c-Fms, and that (2) TNF-␣ derived from BM CD45 Ϫ CD34 Ϫ stromal cells growthcontrolled by Ang II specifically regulates the c-Fms expression in promonocytes (CD11b high Ly-6G low ), thus leading to the increased numbers of circulating monocytes that modulate AT 1 -mediated proatherogenic activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, the relative contribution of the BM renin-angiotensin system to hypercholesterolemia-associated monocytosis has not been fully investigated. 12 In the present study, we focused on the action of the AT 1 receptor expressed in BM cells and studied whether (1) Ang II affects the differentiation/proliferation from BM stem cells into monocyte-lineage cells, and (2) hypercholesterolemiaassociated monocytosis contributes to the development of AT 1 -mediated atherosclerosis. Our results demonstrated for the first time that (1) Ang II promotes M-CSF-induced differentiation from hematopoietic stem cells (HSCs; c-Kit ϩ Sca-1 ϩ Lin Ϫ ) into monocyte-lineage cells through upregulation of the M-CSF receptor c-Fms, and that (2) TNF-␣ derived from BM CD45 Ϫ CD34 Ϫ stromal cells growthcontrolled by Ang II specifically regulates the c-Fms expression in promonocytes (CD11b high Ly-6G low ), thus leading to the increased numbers of circulating monocytes that modulate AT 1 -mediated proatherogenic activities.…”
mentioning
confidence: 99%
“…11 However, the relative contribution of the BM renin-angiotensin system to hypercholesterolemia-associated monocytosis has not been fully investigated. 12 In the present study, we focused on the action of the AT 1 receptor expressed in BM cells and studied whether (1) Ang II affects the differentiation/proliferation from BM stem cells into monocyte-lineage cells, and (2) …”
mentioning
confidence: 99%
“…Previous studies have shown that the regulation of CD11b on monocytes by Ang II is increased or unchanged. Treatment of hypercholesterolemic monkeys with the angiotensin type I receptor antagonist losartan for 15 weeks suppressed peripheral blood and bone marrow monocyte CD11b expression [40]. Circulating monocytes from hypertensive patients showed an increased monocyte adhesion to endothelial cells and an increased expression of CD11b.…”
Section: Discussionmentioning
confidence: 97%
“…The finding that Ang II functions as an obligatory mediator pathway for the formation of aortic fatty streaks in the presence of hypercholesterolemia and no changes in arterial pressure was first demonstrated in monkeys 36 . These findings led to the hypothesis that the RAAS is a critical contributor to the pathogenesis of atherosclerosis through stimulation of oxidative stress, inflammatory cytokines, and recruitment of monocytes into the subendothelial vascular spaces 3639 . Proatherogenic aldosterone mechanism occurs via induction of oxidative stress, endothelial dysfunction, activation of adhesion molecules, and up-regulation of ACE and AT 1 receptors (see 27 for review).…”
Section: Introductionmentioning
confidence: 99%